Use of industrial waste in prenursery stage of oil palm (Elaeis guineensis, Arecaceae) production: growth and nutrient uptake (UNED Research Journal, 2018)
Oil palm is an important crop in need of improved production methods. We evaluated industrial waste for variety Deli x Nigeria in pre-nurseries: volumetric mixtures (10 and 20%) of oil palm empty fruit bunch (EFB), industrial sludge and industrial ash with soil (80 and 90%). Nursery bags were filled with mixture in a restricted randomized block design. The variables were evaluated at 45 and 90 days after planting. We found that 80% soil +20% EFB treatment (S20F) increased leaf length and diameter, biomass, bulb diameter and root length. It also increased nutrient uptake in all mixtures. The concentration of Mg, K, P, Zn and S was higher than in soil. Industrial waste allows a significant reduction in fertilizer for pre-nurseries.
Keywords: Oil palm empty fruit bunch; industrial sludge; industrial ash; oil palm nursery; Deli x Nigeria; compost